A case report of atypical chronic myeloid leukemia with complete hematological and major molecular response to Venetoclax/Azacitidine treatment - Chen, Hongxia; Wang, Ning; Li, Yin; Xie, Xiaohong; Yang, Yi (Frontiers in Oncology, 2024)
Atypical Chronic Myeloid Leukemia (aCML), a myeloproliferative neoplasm with poor prognosis, was reclassified as aCML by the ICC classification, and as MDS/MPN with neutrophilia by the WHO 2022 classification. Due to the heterogeneity of its clinical features and the lack of unique biomarkers, as well as limited treatment options, aCML currently lacks a standardized treatment protocol. In this case report, we reviewed a young man diagnosed with aCML who achieved complete clinical and hematologic remission subsequent to receiving a therapeutic regimen combining Venetoclax and Azacitidine.